Elderly as a vulnerable group: a legal review in Malaysia - Shazreen Nadia Zulkipli; Ramalinggam Rajamanickam; Muhamad Helmi Md Said (Penerbit Universiti Kebangsaan Malaysia, 2025)
Malaysia is experiencing significant demographic changes with a rapidly increasing elderly population. According to the Department of Statistics Malaysia, the percentage of citizens aged 60 and above is expected to exceed 15% by 2030. This demographic shift underscores the urgent need to address the welfare and protection of the elderly. This article aims to examine the position of the elderly as a vulnerable group in terms of legal protections in Malaysia by reviewing the specific legislation and policies for the elderly, including laws that provide for their protection, care, and welfare as well as comparing the legal position of the elderly with other vulnerable groups. Using a qualitative research methodology involving legal analysis, this article examines the existing legal framework intended to protect the rights and well-being of the elderly, identifying weaknesses and shortcomings in the legal system. This article also proposes necessary improvements to ensure more comprehensive and effective protection while emphasizing the importance of having strong legal provisions to address issues such as abuse, neglect, and financial exploitation. The findings of this study are expected to provide useful guidance for policymakers and legislators in their efforts to strengthen legal protection for the elderly in Malaysia.